Naja sputatrix Venom Preconditioning Attenuates Neuroinflammation in a Rat Model of Surgical Brain Injury via PLA2/5-LOX/LTB4 Cascade Activation - Yuechun Wang (Nature Portfolio, 2017)
Abstract Inflammatory preconditioning is a mechanism in which exposure to small doses of inflammatory stimuli prepares the body against future massive insult by activating endogenous protective responses. Phospholipase A2/5-lipoxygenase/leukotriene-B4 (PLA2/5-LOX/LTB4) axis is an important inflammatory signaling pathway. Naja sputatrix (Malayan spitting cobra) venom contains 15% secretory PLA2 of its dry weight. We investigated if Naja sputatrix venom preconditioning (VPC) reduces surgical brain injury (SBI)-induced neuroinflammation via activating PLA2/5-LOX/LTB4 cascade using a partial frontal lobe resection SBI rat model. Naja sputatrix venom sublethal dose was injected subcutaneously for 3 consecutive days prior to SBI. We observed that VPC reduced brain edema and improved neurological function 24 h and 72 h after SBI. The expression of pro-inflammatory mediators in peri-resection brain tissue was reduced with VPC. Administration of Manoalide, a PLA2 inhibitor or Zileuton, a 5-LOX inhibitor with VPC reversed the protective effects of VPC against neuroinflammation. The current VPC regime induced local skin inflammatory reaction limited to subcutaneous injection site and elicited no other toxic effects. Our findings suggest that VPC reduces neuroinflammation and improves outcomes after SBI by activating PLA2/5-LOX/LTB4 cascade. VPC may be beneficial to reduce post-operative neuroinflammatory complications after brain surgeries.